HUBUNGAN KOMPONEN HASIL DAN HASIL TERHADAP LIMA VARIETAS UNGGUL BARU (VUB) KEDELAI (Glycine Max (L) Merril) PADA LAHAN KERING DI PROVINSI PAPUA BARAT - Apresus Sinaga (Bernas : Jurnal Penelitian Pertanian, 2016)
This study aimed to geting information about the relationship among the characters and identifying characters agronomic direct and indirect influence on grain yield. Many as four varieties of soybean (Glycine max) included the local varieties as comparison was evaluated on dry land land in Manokwari, Sobey District, Village Sobey at MT I month from January to December, 2013. The experiment was conducted by using a randomized block design (RAK) non factorial, with three blocks as replication. The variable agronomic characters were observed terms of height, the number of productive branches, number ofpods per plant, number of empty pods per plant, total number of pods, and the results. Data were analyzed with simple correlation and continued with path coefficient analyses. The results based on both method of analysis, soybean varieties of high yielding varieties which had total number of pods and a high number of pods. Therefore, the total number of pods and number of pods were recommended to be used as selection criteria in order to obtain soybean varieties for high yield in dry land.